2013
DOI: 10.1371/annotation/b53a0b8b-3eb6-44a2-9c37-bc9bb66bfe7e
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Traditional Chinese Medicine in Cancer Care: A Review of Controlled Clinical Studies Published in Chinese

Abstract: Background: Traditional Chinese medicine (TCM) has been widely applied for cancer care in China. There have been a large number of controlled clinical studies published in Chinese literature, yet no systematic searching and analysis has been done. This study summarizes the current evidence of controlled clinical studies of TCM for cancer. Methods:We searched all the controlled clinical studies of TCM therapies for all kinds of cancers published in Chinese in four main Chinese electronic databases from their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Another concern raised from scientists and physicians is whether CHM would have an influence on the pharmacokinetics or anti-cancer effect of chemotherapeutic regimens when used in combination (92). In some animal studies, it is reported that some of CHM such as berberine showed no interaction with chemotherapeutic agents and did not reduce the anti-tumor efficacy (93)(94)(95). In clinic trials, however, few studies performed pharmacokinetics evaluation of chemotherapeutic agents in patients receiving CHM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another concern raised from scientists and physicians is whether CHM would have an influence on the pharmacokinetics or anti-cancer effect of chemotherapeutic regimens when used in combination (92). In some animal studies, it is reported that some of CHM such as berberine showed no interaction with chemotherapeutic agents and did not reduce the anti-tumor efficacy (93)(94)(95). In clinic trials, however, few studies performed pharmacokinetics evaluation of chemotherapeutic agents in patients receiving CHM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese medicine has been paid more and more attention by doctors and patients. For patients who have received systemic adjuvant chemotherapy, traditional Chinese medicine treatment can effectively combine with western medicine to alleviate toxic side effects caused by chemotherapy drugs, such as blood cell reduction, nausea, vomiting, diarrhea, rash, hair loss, fatigue, etc [7][8] . Many laboratory studies have shown that crude extracts of Chinese herbal medicines and active ingredients can inhibit BC cell proliferation and migration, induce apoptosis of breast cancer cells in vitro, and reduce the side effects of chemotherapy drugs [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%